Private Notes on Gary Becker - James J. Heckman (Institute for the Study of Labor (IZA), 2014)
This paper celebrates the life and contributions of Gary Becker (1930-2014).
Keywords: B31; J24; 330; human capital; human behavior; lifetime contributions; tribute